Light-years [compact disc ] - Nas (Musician); DJ Premier, 1966- (Mass Appeal, 2026)
Two legends, one record. Nas links with DJ Premier for the legendary Hip Hop release that fans have been anticipating for years. It's a must-have addition for any serious collection.